Self-powered trajectory-tracking microsystem based on electrode-miniaturized triboelectric nanogenerator. (April 2021) - Ba, Yan-Yuan; Bao, Jing-Fu; Wang, Zhi-Yong; Deng, Hai-Tao; Wen, Dan-Liang; Zhang, Xin-Ran; Tu, Cheng; Zhang, Xiao-Sheng
Abstract: As an emerging ambient energy harvesting technology, triboelectric nanogenerators (TENGs) have been proven as robust power sources, and furthermore self-powered electronics which are promising to construct human-machine interfaces due to the unique feature of the integration of powering itself and functionalities. Several technologies have been proposed to improve the properties of TENGs, but most of them focus on the interface of triboelectric pair and rarely on another key component, the electrodes. Here, a new configuration of TENG array based on the electrode-miniaturized strategy is developed. The effects of the electrode miniaturization on the electrical output, optical transmittance and signal interference are comprehensively investigated through experimental measurements. It reveals that two-third reduction in the electrode area only exhibits a slight effect on the electrical output of TENG, in other words the proposed electrode-miniaturized TENGs (EM-TENGs) keep highly consistent while the electrode area tuning in the range of 33–100%. Moreover, this electrode-miniaturized strategy endows TENGs two more significant benefits, including higher light transmittance and lower signal interference, which makes it show much greater potential in the field of self-powered smart microsystems, especially in need of remarkable optical properties. Therefore, a human-machine interaction microsystem for trajectory tracking is successfully demonstrated, which is self-powered, transparent and flexible. Graphical Abstract: ga1 Highlights: A new configuration of TENG array based on the electrode-miniaturized strategy (EM-TENG) is developed. EM-TENGs show two advantages of further enhanced optical property and signal isolation while electric output well preserved. A transparent human-machine interaction microsystem is demonstrated to accurately monitor the trajectory of moving targets.